Micromesh bottle / Mohamad Shah Ahmad ...[et al.] - Ahmad, Mohamad Shah; Datu Nassal, Datu Muammar; Azminudin, Muhamad Amirullah; Anak Bereng, Caynillen Mooray; Junni, Rolnny (2016)
The team will develop a bottle water for recreation used that will help many sport man in their activity. This bottle can regenerate water through the condensation process. The bottle water will fill water by trapping the humidity from surrounding environment. The users will be provide with fresh water to them without any worries from any chemical substance. This product concept mostly helps the climbers, biker, hikers, and many more outdoor activities. This bottle gives you the freedom to plan your adventure without worrying about the most elemental component of survival: water supply.